Analyzing the relationship of RNA and DNA methylation with gene expression - Shangqian Xie; Darren Hagen; Gabrielle M. Becker; Kimberly M. Davenport; Katie A. Shira; Morgan R. Stegemiller; Jacob W. Thorne; Sarem Khilji; Denise Konetchy; Patricia Villamediana; Brenda M. Murdoch; Stephanie D. McKay (Genome Biology)
Abstract Background DNA 5-methylcytosine (5mC) and RNA N6-methyladenosine (m6A) methylation are prevalent modifications in eukaryotes, both playing crucial roles in gene regulation. Recent studies have explored their crosstalk and impact on transcription. However, the intricate relationships among 5mC, m6A, and gene expression remain incompletely elucidated. Results We collect data on 5mC, m6A, and gene expression from samples from three tissues from each of four pregnant cattle and sheep. We construct a comprehensive genome-wide self-interaction (same gene) and across-interaction (across genes) network of 5mC and m6A within gene-bodies or promoters and gene expression in both species. Qualitative analysis identifies uniquely expressed genes with specific m6A methylation in each tissue from both species. A quantitative comparison of gene expression ratio between methylated and unmethylated genes for m6A within gene body and promoter, and 5mC within gene body and promoter confirms the positive effect of RNA methylation on gene expression. Importantly, the influence of RNA methylation on gene expression is stronger than that of DNA methylation. The predominant self- and across-interactions are between RNA methylation within gene bodies and gene expression, as well as between RNA methylation within promoters and gene expression in both species. Conclusions RNA methylation has a stronger effect on gene expression than does DNA methylation within gene bodies and promoters. DNA and RNA methylation in gene-bodies has a greater impact on gene expression than those in promoters. These findings deepen comprehension of the dynamics and complex relationships among the epigenome, epitranscriptome, and transcriptome, offering fresh insights for advancing epigenetics research.